A Comparative Analytical Study of Krishna Musali Choorna and Krishna Musali Kshara (International Journal of Ayurveda and Pharma Research, 2023)
Krishna Musali (Curculigo orchioides) is among the Dashapushpa, a group of ten herbs which is culturally and medically important to the people of Southern India, especially in Kerala. Krishna Musali is mentioned in various context in the names of Krishna Musali, Talapatri, Talamooli etc. and it is having Madhuratikta rasa, Ushna virya and it is Vatapittahara and Rasayana properties. In classics references about this drug can be seen in the context of Dhoomapana yoga, Kshara vidhi, Ekangasopha chikitisa etc and the Acharyas were categorized in to specific Gana or Varga based on its mode of action.  Krishna Musali Choorna and Kshara prepared based on the method of preparation mentioned in Sharangadhara Samhita. Analytical study was carried out for the purpose of standardization. For the qualitative assurance of the raw material analytical study provides the objective parameters for the standardization leading to a reproducible quality. These tests were done for evaluating the anticancer activity of Krishna Musali Choorna and Kshara in cervical cancer cell lines. The preliminary phytochemical study shows high alkalinity of Krishna Musali Kshara compared to Choorna, it supports the definition of alkali of being caustic and corrosive in nature. So, it will be helpful in the treatment of early stages of Cervical carcinoma.